Predictors of mortality among newborns admitted with perinatal asphyxia at public hospitals in Ethiopia: a prospective cohort study - Samuel Dessu; Zinabu Dawit; Abebe Timerga; Muluken Bafa (BMC, 2021)
Abstract Introduction Perinatal asphyxia is a complicated newborn health problem and applies a high contribution to the increased proportion of newborn mortality. It occurs in newborns due to altered breathing or inadequate inhalation and exhalation resulting in reduced oxygen perfusion to certain body tissues and organs. Irrespective of the increased progress in health care towards newborns and implementations in reductions in under-five, infant, and neonatal mortality in the past 10 years, perinatal asphyxia remained as the most common severe newborn health challenge that causes a high number of morbidity and mortality. Methods A prospective cohort longitudinal study was implemented among 573 newborns admitted with perinatal asphyxia at public hospitals in Southern Ethiopia from 1st March 2018 to 28th February 2020. The perinatal survival time was determined using Kaplan Meier survival curve together with a log-rank test. The dependent variable was time to death and the independent variables were classified as socio-demographic factors, obstetrics related factors, newborn related factors and maternal medical related factors. The study subjects were entered in to the cohort during admission with perinatal asphyxia in the hospital and followed until 7 days of life. Results The cumulative proportion of survival among the newborns admitted with perinatal asphyxia was 95.21% (95%CI:91.00,97.48), 92.82% (95%CI:87.95,95.77), 92.02%(95%CI:86.84,95.22) and 90.78%(95%CI:84.82,94.48) at the end of first, second, third and fourth follow-up days respectively. The mean survival date was 6.55(95%CI: 6.33, 6.77) and cord prolapse (AHR:6.5;95%CI:1.18,36.01), pregnancy induced hypertension (AHR:25.4;95%CI:3.68,175.0), maternal iron deficiency anemia (AHR:5.9;95%CI:1.19,29.5) and having convulsion of the newborn (AHR:10.23;95%CI:2.24,46.54) were statistically significant in multivariable cox proportional hazard model. Conclusion The survival status among newborns with perinatal asphyxia was low during the early follow-up periods after admission to the hospital and the survival status increased after fourth follow up days. In addition, cord prolapse, history of PIH, maternal iron deficiency anemia and newborns history of convulsion were the independent predictors of mortality.